ANTIBACTERIAL ACTIVITY OF ETHANOLIC EXTRACT BAWANG DAYAK (ELEUTHERINE BULBOSA (MILL.) URB) IN CREAM AGAINST PROPIONIBACTERIUM ACNES - ARDHANY, SYAHRIDA DIAN; NOVARYATIIN, SUSI (International Journal of Applied Pharmaceutics, 2019)
Objective: The aims of this present study were to formulate antiacne cream consisting ethanolic extract of bawang dayak and evaluate antibacterial activity of cream on day 0 and day 7 to see stability activity and preparation. Methods: Cream formula of bawang dayak was evaluated organoleptic characteristics, homogeneity, pH, adhesion test, dispersion test, and in vitro antibacterial against Propionibacterium acnes. Results: The results of evaluate cream homogeneity were F3 and F4 on day 7 separate and non-homogen but all formula pH suitable for topical application. On day 0, F1 and F2 shown antibacterial activity in category weak activity, F3 and F4 in category moderate activity, while on day 7 all formula have antibacterial activity in category weak activity. Conclusion: All cream formula potentials inhibit against P. acnes but this research must be improved both of preparation and stability activity.